Pembuatan Grease Dari Minyak Jelantah: Pengaruh Nisbah Mol LiOHNaOH Dan Nisbah Base Oil-Thickening Agent Terhadap Karakteristik Grease - Rizky Sandy Harahap; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Greases are used between rubbing metal surfaces to reduce friction. The utilized base oil could be vegetable oir or mineral oil. The objective of this research are to produce greasefrom waste cooking oil and to study the LiOH-NaOH ratio and base oil effect to grease characteristics. Grease-making methods comprised base oil (waste cooking oil) preparation, saponification to made thickening agent, and blending process with stirring speed 650 rpm among thickening agent, base oil and additive for the grease-making. The variations used were LiOH-NaOH ratio (90:10; 80:20; 70:30) and base oil:thickening agent ratio (75:20; 77,5:17,5; 80:15; 82,5:12,5; 85:10). The test methods conducted were penetration test ASTMD217 for grease consistency and dropping point ASTM D566. The best grease obtained belong to grease specification and performance parameter for NLGI grade A quality levelwith thickening agent formulation LiOH:NaOH ratio 90:10 and grease formulation base oil:thickening agent ratio 75:20 with penetration 227 (0,1 mm), NLGI number 3 (25 oC) anddropping point 139 oC.Keyword : dropping point test, grease, penetration test, waste cooking oil.